The Influence of Followed Nouns - Daoud, Bahiya Ahmad Abdullah; Rabba, Mohammad Ali Younos (Journal of Arabic Language Sciences and Literature, 2023)
This study aims to shed light on the location of the words that follow nouns in accordance with their association with the noun that they follow in a sentence, along with the relation to the diacritical marks that will be used in the word. The proximity of the followed noun to its follower affects the diacritic mark used within the word. The topic of words that follow nouns is one of the most important and vast topics in grammar, for it has multiple routes, multifunction’s, and branching issues. Hence, this study came to exhibit the ways grammarians used in placing the diacritical mark of those followers according to the level of the followed noun, to grovel its stray, and to collect its scattered; this can be done through induction, presentation, and discussion. There is no dispute that the nature of this study requires the use of the inductive analytical method as its core center, for the researcher had inducted examples and models that are scattered in the books of grammar and, on top of them, the holy book of grammar, The Kitab by Sibawayh.